Ultrasound guided transvaginal follicular aspiration technique for chronic follicular cyst in a Holstein Friesian crossbred cow - C. Pugazharasi; T. Sarath; N. Arunmozhi; R. Sureshkumar; U. S. Kalyaan; K. Krishnakumar; S. Balasubramanian (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A ten-year-old pluriparous crossbred cow with the history of prolonged estrus signs was presented to the Madras Veterinary College Teaching Hospital. Per rectal examination revealed follicular cyst in the right ovary. On real-time ultrasonography, a large anechoic follicle and multiple follicles were visualized in the right and left ovary, respectively. The case was diagnosed as Cystic Ovarian Degeneration due to follicular cyst and treated with 20μg-GnRH intramuscularly. Re-examination after 10 days revealed persisted cyst on right ovary and even after second GnRH, the condition persisted. Further, the cow was treated with PGF2α @ 500μg intramuscularly but cysts the persisted. Then, the cyst was punctured and follicular fluid aspirated through ultrasound guided transvaginal probe with a needle and about 12 ml of follicular fluid was recovered but the cyst recurred again. Hence, from the study it was concluded that the case was non-responsive for either hormonal therapy or ultrasound guided transvaginal follicular aspiration which might be due to its chronic, secretory nature and thus the prognosis remains poor.